Academic Resilience of Bullied Students: Role of Peer Attachment and Internal Locus of Control - Tsabita, Nafisa Ainur; Ruby, Arcivid Chorynia (World Psychology, 2025)
Bullying in Islamic boarding schools is a serious issue that negatively impacts students' psychological well-being and academic performance. Academic resilience plays a crucial role in helping students cope with the pressure caused by bullying. This study aims to examine the relationship between peer attachment and internal locus of control with academic resilience in students who have experienced bullying. This research employed a quantitative correlational method with 100 respondents selected through purposive sampling. The instruments used include a peer attachment scale, an internal locus of control scale, and an academic resilience scale developed by the researcher. Data analysis revealed a significant positive relationship between peer attachment and internal locus of control with academic resilience. These findings highlight the importance of supportive peer relationships and personal control in strengthening students' academic adaptability. The implications of this study suggest the need for interventions focusing on peer dynamics and personal empowerment within educational environments.